Golgi scaffold protein PAQR11 in pan-cancer landscape: A comprehensive bioinformatics exploration of expression patterns, prognostic significance, and potential immunological function - Zhu Liu; Zhi-Qiang Ling (Heliyon)
Background: The progestin and adipoQ receptor family member, PAQR11, is recognized for its roles in vesicle trafficking, mitogenic signaling, and metastatic spread, positioning it as a crucial regulator in cancer biology. PAQR11 influences lipid metabolism and susceptibility to ferroptosis in cancer cells. This study aims to investigate the prognostic significance of PAQR11, its relevance to immune responses, and its association with drug sensitivity across various cancer types. By elucidating these aspects, the research seeks to assess PAQR11's potential as a biomarker and therapeutic target in oncology. Methods: We conducted a comprehensive bioinformatics analysis using publicly available pan-cancer datasets from TCGA, GEO, UALCAN, TIMER, GEPIA2, KM plotter, and TISIDB. This analysis encompassed gene expression profiles across 33 cancer types, with a focus on PAQR11's expression patterns, prognostic significance, and immunological relevance. In addition, the study explored the correlation between PAQR11 expression and drug sensitivity, alongside its molecular and pathological characteristics in various tumors. Results: Our findings demonstrate elevated PAQR11 expression levels across multiple cancer types, which significantly correlate with patient prognostic outcomes. The analysis further revealed PAQR11's involvement in immunological and epigenetic processes, underscoring its critical role in cancer progression and treatment response. Notably, a strong correlation between PAQR11 expression and drug sensitivity was identified, suggesting its potential influence on the initiation and progression of various cancers and highlighting its promise as a therapeutic target. Conclusions: The comprehensive analysis of PAQR11 underscores its significance as a biomarker for cancer prognosis and its role in regulating immunological and epigenetic processes. These findings offer valuable insights that could inform early detection strategies and the development of novel therapeutic approaches. Further exploration and validation of PAQR11 are essential, highlighting the need for its integration into future oncological research and treatment strategy development. Trial registration: Not applicable.